Metabolic syndrome and neurological disorders - Farooqui, Akhlaq A.; Farooqui, Tahira (Wiley-Blackwell, 2013)
"Metabolic Syndrome and Neurological Disorders brings together information on the cluster of common pathologies which cause metabolic syndrome - abdominal obesity linked to an excess of visceral fat, insulin resistance, dyslipidemia and hypertension - to provide a comprehensive and cutting edge exploration of the link between metabolic syndrome and neurological disorders. Metabolic syndrome is recognized to play a role in neurological disorders such as stroke, Alzheimer's disease, and depression. For the first time in book form, Metabolic Syndrome and Neurological Disorders covers the molecular mechanisms thought to underlie this mirror relationship, as well as how lifestyle and other factors such as oxidative stress and inflammation may play a role in the disease. Grounded in a series of epidemiological studies of metabolic-cognitive syndrome, this book will be a valuable reference for researchers, dietitians, nutritionists, and physicians"--Provided by publisher.